The effect of the processing way of technogenic raw materials on the properties of gypsum binding materials - Leškevičienė, Violeta; Nizevičienė, Dalia; Valančius, Zenonas (Journal of Civil Engineering and Management, 2003)
Since natural gypseous raw materials are not available in Lithuania, the production of gypseous binding materials is feasible only from different process waste. In the work the results of investigations conducted on a gypseous binding material are presented, which is produced from dehydrate and semihydrate calcium sulphate (phosphogypsum) formed in JSC “Lifosa” and from gypsum forms of waste obtained in JSC “Jiesia”. The processing of dehydrate phosphogypsum into gypseous binding materials has been thoroughly investigated and the created technologies have been tested in several enterprises. In 1998 in JSC “Lifosa” dehydrate technology was changed over semihydrate technology. In the work the ways of producing gypseous binding material or gypsum products are presented, which meet the requirements of the standards being in effect. For the above ways of production Lithuanian patent LT 4699 B, 2000 09 25 has been obtained. In JSC “Jiesia” several tons of gypsiferous waste are produced daily. The investigation results enable us to infer that it is feasible to obtain rather qualitative b and a semi-hydrate gypsum from gypseous waste without additional processing and with comparatively insignificant energy consumption.First Published Online: 26 Jul 2012